Recruiting Intensity and Hiring Practices: Cross-Sectional and Time-Series Evidence - Benjamin Lochner; Christian Merkl; Heiko Stüber; Nicole Gürtzgen (ZBW - Leibniz Information Centre for Economics, 2020)
Using the German IAB Job Vacancy Survey, we look into the black box of recruiting intensity and hiring practices from the employers' perspective. Our paper evaluates three important channels for hiring -namely vacancy posting, the selectivity of hiring (labor selection), and the number of search channels- through the lens of an undirected search model. Vacancy posting and labor selection show a U-shape over the employment growth distribution. The number of search channels is also upward sloping for growing establishments, but relatively flat for shrinking establishments. We argue that growing establishments react to positive establishment-specific productivity shocks by using all three channels more actively. Furthermore, we connect the fact that shrinking establishments post more vacancies and are less selective than those with a constant workforce to churn triggered by employment-to-employment transitions. In line with our theoretical framework, all three hiring margins are procyclical over the business cycle.
Keywords: E24; J63; 330; recruiting intensity; vacancies; labor selection; administrative data; survey data